2016
DOI: 10.1074/jbc.m116.715748
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor 3 (KLF3/BKLF) Is Required for Widespread Repression of the Inflammatory Modulator Galectin-3 (Lgals3)

Abstract: The Lgals3 gene encodes a multifunctional ␤-galactosidebinding protein, galectin-3. Galectin-3 has been implicated in a broad range of biological processes from chemotaxis and inflammation to fibrosis and apoptosis. The role of galectin-3 as a modulator of inflammation has been studied intensively, and recent evidence suggests that it may serve as a protective factor in obesity and other metabolic disorders. Despite considerable interest in galectin-3, little is known about its physiological regulation at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Interestingly, we have found the 9aaTAD activation domain in Crassostrea gigas, KLF1 ortholog (9aaTAD sequence ELL DYD FIL, gene ID; EKC39171), which closely resembles the first identified 9aaTAD in activator Oaf1 (9aaTAD sequence DLF DYD FLF) (12). Surprisingly, the 9aaTAD activation domains of KLF3 and KLF8 did not activate transcription, which correlated with their repressor function reported previously (52,(81)(82)(83)(84). The accumulation of valines has been shown here again to be associated with the 9aaTAD deactivation (Figures 7).…”
Section: Klf Homology With the Sp Family Revealed Their Activation Dosupporting
confidence: 81%
“…Interestingly, we have found the 9aaTAD activation domain in Crassostrea gigas, KLF1 ortholog (9aaTAD sequence ELL DYD FIL, gene ID; EKC39171), which closely resembles the first identified 9aaTAD in activator Oaf1 (9aaTAD sequence DLF DYD FLF) (12). Surprisingly, the 9aaTAD activation domains of KLF3 and KLF8 did not activate transcription, which correlated with their repressor function reported previously (52,(81)(82)(83)(84). The accumulation of valines has been shown here again to be associated with the 9aaTAD deactivation (Figures 7).…”
Section: Klf Homology With the Sp Family Revealed Their Activation Dosupporting
confidence: 81%
“…KLF3 has the potential to play numerous roles in a resident population. KLF3 −/− mice show significantly increased production of galectin-3, a mediator of diverse actions including chemotaxis and inflammation (66). Thus, the downregulation of KLF3 further supports brain CD103 + T cells being non-circulating or a highly pro-inflammatory population.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture and transfection. Bone marrowderived macrophages were harvested from femora and tibiae as previously described (24). Equal numbers of WT and Klf3 -/-BMDMs were seeded for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…KLF3 has been well-established as a key transcription factor in red blood cell development (21)(22)(23), however, the Klf3 -/mouse lacks a severe erythropoietic phenotype. It has recently been shown that KLF3 regulates expression of the inflammatory modulator galectin-3 (24) and is also involved in B cell maturation (25), suggesting a possible link between KLF3, immune cell function and inflammation.…”
mentioning
confidence: 99%
See 1 more Smart Citation